I-potty pro: enhancing toilet independence through interactive support for preschool children - Alias, Noor Amiera; Kadar, Masne; Wan Yunus, Farahiyah; Cremin, Katie; Abdul Zalif, Nurul Ku Harmila (Faculty of Pharmacy, 2025)
Teaching self-care independence, specifically toilet training, is crucial for preparing children for school readiness. However, parents and teachers often lack effective tools to guide children through this essential developmental milestone. I-Potty Pro offers an innovative solution with an occupational therapy-based approach to toilet training. What makes it unique is the integration of evidence-based strategies, techniques, and approaches not found in traditional tools. I-Potty Pro directly addresses delayed toilet independence, which can negatively affect a child's confidence and school readiness. It serves as an educational tool for parents, caregivers, and teachers, promoting self-care skills in preschool children through structured, interactive guidance. By leveraging technology, I-Potty Pro fosters independence while advancing early childhood development practices. A cognitive interview approach was conducted with three parents and two teachers to access the app's usability.results revealed that I-Potty Pro is "time-efficient" and "accessible ubiquitously by both parents and teachers". The app's scalability makes it suitable for widespread use in preschools, day care and homes. Further study will be conducted to evaluate the effectiveness of the I-Potty Pro application, providing empirical evidence to support its commercialization.